Immobilization of cobalt ions using hierarchically porous 4A zeolite-based carbon composites: Ion-exchange and solidification. (February 2020) - Al-Jubouri, Sama M.; Holmes, Stuart M.
Graphical abstract: Highlights: The effect of boundary film reduced and the intra-particle diffusion of ions enhanced using 4A zeolite/carbon composites. The kinetics of the cobalt ion-exchange was investigated. Encapsulation of cobalt ion achieved via vitrification. Abstract: The efficacy of the synthesized 4A zeolite and the 4A zeolite-based carbon composites were examined for the removal of cobalt ions from an aqueous solution by ion-exchange. Two types of agricultural waste were chosen as precursors to prepare the porous supports for composites synthesized at hydrothermal conditions. The maximum exchange capacity of zeolite portions present in 4A zeolite/Almond shells carbon (AAS) and 4A zeolite/Walnut shells carbon (AWS) reached to 235.175 and 202.887 mg ion/g zeolite; but it reached to 99.525 mg ion/g zeolite for 4A zeolite (A) at same conditions. Removal of cobalt ions by ion-exchange process enhanced when the temperature and pH of the cobalt solution increased. The equilibrium data are precisely fitted by the Freundlich model with a correlation factor (R 2 ) of 0.9807, 0.9859 and 0.9857 for A, AAS and AWS. The cobalt uptake by zeolite-based carbon composites process is controlled by ion-exchange. The Weber and Morris intra-particle diffusion kinetics and Boyd model equations confirmed enhancement of cobalt removal using the composites. The seepage of cobalt ions from the solidified ion-exchangers encapsulating ions reduced to 0.01 ppm in H2 O and to 0.05-0.25 ppm in 0.5 N NaCl solution.